Structural insights into membrane proteins, membrane protein-lipid interactions and drug metabolites in the gas-phase from ion mobility mass spectrometry - Reading, E (2014)
Investigating the structures of membrane proteins and their interactions with lipids remains challenging for well-established biophysical techniques. In this thesis the use of mass spectrometry (MS) and ion mobility (IM) spectrometry were explored for the interrogation of membrane proteins, their stoichiometry, stability and interactions with lipids. The techniques used were also applied to the identification of drug metabolites. In the first two chapters reviews of both mass spectrometry methods, and membrane protein biogenesis and membrane protein-lipid interactions are presented. The first challenge for studying membrane proteins by MS was to optimise solution conditions. A detergent screening strategy was developed for this purpose (Chapter 3). The various detergent environments studied revealed dramatic differences in mass spectral quality permitting investigation of membrane protein-lipid interactions. Changes were observed in the electrospray charging of membrane proteins and trends were established from an extensive collection of membrane proteins ejected from a wide variety of detergent environments. The physicochemical principles behind the MS of membrane proteins were deduced and are presented (Chapter 4). The results of these experiments led to a deeper understanding of the ionisation processes and the influence of detergent micelles on both charge state and release mechanisms. Experiments from a range of different micelles also allowed the influence of charge and its effects on the preservation of native-like membrane protein conformations to be monitored by IM-MS. By resolving lipid-protein interactions, and by monitoring the effects of lipid binding on the unfolding of three diverse membrane protein complexes, substantial differences in the selectivity of membrane proteins for different lipids were revealed (Chapter 5). Interestingly lipids that stabilised membrane proteins in the gas-phase were found to induce modifications in structure or function thus providing an approach to assess direct lipid contributions, and to rank order lipids based on their ability to modulate membrane proteins. Using the MS approaches developed here also enabled study of the diversity of oligomeric states of the mechanosensitive channel of large conductance (MscL) (Chapter 6). Results revealed that the oligomeric state of MscL is sensitive to deletions in its C-terminal domain and to its detergent-lipid environment. Additionally, a case study with GlakoSmithKline (GSK) was undertaken using IM-MS technology but in this case applied to the identification of drug metabolites (Chapter 7). The results showed that IM-MS and molecular modelling could inform on the identity of different drug metabolites and highlights the potential of this approach in understanding the structure of various drug metabolites.